2021
DOI: 10.1177/02692163211022184
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine: Procedural sedation in palliative care: A case report

Abstract: Background: This report describes the use of intranasal dexmedetomidine to control incident pain and facilitate daily change of dressing in a patient with cutaneous breast cancer. Case presentation: A 45-year-old woman with extensive thoracic cutaneous metastatic bilateral breast cancer requiring daily 2-hour dressing changes to manage significant exudate. Pain during change of dressing was severe and unresponsive to usual analgesics. Deeper sedation was not an option as the patient was required to change posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Treatment procedures, such as the placement of the NSC patch through the nasal cavity, cause anxiety and pain and lead to violent resistance and difficulty cooperating with the treatment. Some studies have shown that moderate sedation and sleep deprivation can effectively ensure the accuracy of examination results without motion imaging and smooth treatment progress (31,32). The nurses in this study used phenobarbital, chloral hydrate, and other drugs to sedate the children gradually, according to the doctor's advice, and closely observed the status of the children during the sedation period.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment procedures, such as the placement of the NSC patch through the nasal cavity, cause anxiety and pain and lead to violent resistance and difficulty cooperating with the treatment. Some studies have shown that moderate sedation and sleep deprivation can effectively ensure the accuracy of examination results without motion imaging and smooth treatment progress (31,32). The nurses in this study used phenobarbital, chloral hydrate, and other drugs to sedate the children gradually, according to the doctor's advice, and closely observed the status of the children during the sedation period.…”
Section: Discussionmentioning
confidence: 99%
“…The adequate dose of IN DEX to be administered was a challenging choice. One case report suggested that both 1 and 1.5 µg/kg of IN DEX were safe and effective to induce light sedation in the management of complex wound dressings for cutaneous thoracic metastatic bilateral breast cancer in a 45-year-old woman [ 39 ]. The recommended doses of IN DEX varied from 0.5 to 1.5 µg/kg for adults, while the doses commonly reported in children varied from 0.5 to 4 µg/kg [ 13 , 15 , 20 , 23 25 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%